Spectrum of aerobic bacteria and their antimicrobial pattern in blood stream infections of hospitalised patients: a retrospective study - Swamy, M. Anjaneya; Golia, Saroj; Varania, Neelima (International Journal of Research in Medical Sciences, 2018)
Background: Bacteria associated with blood stream infections are an important public health problem which results in morbidity and mortality globally. Emergence of multidrug resistant isolates in hospitalized patients is a major problem. Automation techniques play a major role in early identification of the isolate and its drug susceptibility testing which is important for better outcome of the treatment. This study was aimed to detect the blood stream isolates and their drug susceptibility pattern in hospitalized patients. Methods: This was a retrospective study conducted from 377 records of automated blood culture (bact/alert) and drug susceptibility testing (vitek) results. Positive blood culture bottles were sub cultured to different culture media and the isolates were identified and screened for drug susceptibility testing on Vitek II. Results: Around 20.68% of samples were positive for blood stream infections caused by different pathogens. A total of 78 microorganisms were isolated from 377 samples. Among which gram negative bacilli was observed in 52.56%, gram positive cocci in 44.87% and yeast in 2.56% samples. Coagulase negative staphylococci and Klebsiella pneumoniae were the predominant isolates of the study. Conclusions: Early diagnosis of blood stream infections in hospitalized patients is life saving. Hence a continuous monitoring of isolates and their drug susceptibility is the need of the day.